Prosedur Pengurusan Barang Impor Pada Kantor Pengawasan dan Pelayanan Bea Cukai Tipe Madya Pabean C Langsa Kota Langsa - Refi, T. Muana; Alhabsi, Mohammad (Yayasan Pendidikan Mitra Mandiri Aceh(YPMMA), 2022)
This study aims to determine the procedures for managing imported goods at the Customs Control and Customs Service Office of Intermediate Customs Type C Langsa, Langsa City, which is carried out in the area of the Customs Intermediate Customs Service and Supervision Office of Customs C Langsa, Langsa City with empirical legal research. Data collection techniques are carried out through Field Research (Field Research) where data collection is carried out by observation, interviews, literature studies to related parties at the Customs Supervision and Customs Service Office Type C Langsa Customs, Langsa City so that get accurate data. The data obtained from both primary law and secondary legal materials were analyzed qualitatively and then presented descriptively. The results of the study, in the implementation of the procedure for import activities at the Customs Service and Supervision Office of Customs Type C Langsa, Langsa City, showed that import activities had increased from year to year. The import procedure in Langsa has been stipulated by the government, imports are a concern in spurring economic growth along with the change in the industrialization strategy from an emphasis on import substitution industries to export promotion industries.